Recurrences in the Blanking Period and 12‐Month Success Rate by Continuous Cardiac Monitoring After Cryoablation of Paroxysmal and Non‐Paroxysmal Atrial Fibrillation. (20th March 2017) - PIERAGNOLI, PAOLO; PAOLETTI PERINI, ALESSANDRO; RICCIARDI, GIUSEPPE; CHECCHI, LUCA; GIOMI, ANDREA; MURACA, IACOPO; MANNUCCI, LETIZIA; PADELETTI, LUIGI
Early and Late Recurrences in AF Cryoablation: Introduction: Recurrences within the blanking period (early recurrences) are common after atrial fibrillation (AF) ablation by pulmonary vein isolation (PVI), but their clinical significance is still controversial. We aimed at evaluating the significance of within‐blanking recurrences at 12‐month follow‐up after cryoballoon (CB) PVI, and to assess the real procedural success rate by continuous monitoring of cardiac rhythm. Methods and Results: Sixty consecutive AF patients (34 paroxysmal, 56.7%) underwent their first CB‐PVI at one Italian center (May 2013 to April 2015), and subsequent implantation of an implantable loop recorder (ILR). Overall, 12‐month success rate after the blanking period was 55%. The shortest detected event was 7 minutes long. Late recurrences were more frequent in non‐paroxysmal (19/26, 73.1%) than in paroxysmal AF (8/34, 23.5%; P <0.001). Early recurrences occurred in 17 (28.3%) patients, with 14 also having late recurrences (82.3%), while only 13 out of 43 (30.2%) without within‐blanking recurrences experienced post‐blanking events (P <0.001). Overall, early recurrences showed 51.8% sensitivity (95% CI 31.9–71.3%) and 90.9% specificity (95% CI 75.7–98.1%) for later recurrences, with 82.3% (95% CI 56.6–96.2%) positive and 69.8% (95% CI 53.9–82.8%) negative predictive value. The positive likelihood ratio was 5.7 (95% CI 1.8–17.8). At multivariable analysis, non‐paroxysmal AF (HR: 3.113; 95% CI 1.309–7.403; P = 0.010) and within‐blanking recurrences (HR: 3.453; 95% CI 1.544–7.722; P = 0.003) were independent predictors of post‐blanking AT/AF. Conclusion: CB‐PVI for paroxysmal AF shows a 12‐month success rate of 76.5% after one single procedure, as assessed by continuous cardiac rhythm monitoring. Within‐blanking recurrences predict the ablation failure in more than 80% of patients.